2004
DOI: 10.1080/07315724.2004.10719365
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Nutritional Status on Complications after Major Intraabdominal Surgery

Abstract: Malnutrition is a marker of bad outcomes. Both Subjective Global Assessment and Nutritional Risk Index nutrition tests are predictive for malnutrition and postoperative complications in patients undergoing major abdominal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
171
1
21

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(209 citation statements)
references
References 20 publications
7
171
1
21
Order By: Relevance
“…According to the recent data, there are approximately 30 million individuals with malnutrition or nutritional risk in Europe, and it is estimated that €170 billion is spent annually for this purpose (5). The effects of malnutrition on various organ systems and wound healing have been evaluated in experimental and clinical studies; particularly, its effects on the gastrointestinal system have been emphasized (3,(6)(7)(8). Some clinical studies have indicated lower general complication rates by preoperative nutritional support in patients with malnutrition undergoing major gastrointestinal surgery (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the recent data, there are approximately 30 million individuals with malnutrition or nutritional risk in Europe, and it is estimated that €170 billion is spent annually for this purpose (5). The effects of malnutrition on various organ systems and wound healing have been evaluated in experimental and clinical studies; particularly, its effects on the gastrointestinal system have been emphasized (3,(6)(7)(8). Some clinical studies have indicated lower general complication rates by preoperative nutritional support in patients with malnutrition undergoing major gastrointestinal surgery (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that malnutrition increases postoperative morbidity and mortality and prolongs the length of hospital stay in patients undergoing surgical interventions (1)(2)(3)(4). According to the recent data, there are approximately 30 million individuals with malnutrition or nutritional risk in Europe, and it is estimated that €170 billion is spent annually for this purpose (5).…”
Section: Introductionmentioning
confidence: 99%
“…Among these factors, malnutrition is the most important due to its high prevalence and negative impact on clinical outcomes such as longer hospital stay 3 and mortality. The latter is much more related to malnutrition than cancer alone and can occur in 20% of cases 4 . Approximately half of the patients with malignancies has malnutrition, and in the case of gastrointestinal tract (GIT) tumors, the mortality rate varies from 30% to 50%, reaching 80% in cases of advanced pancreatic cancer 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…The method choice depends on the purpose of the assessment, prognosis or even on the response to nutritional interventions 2,4 .…”
Section: Introductionmentioning
confidence: 99%
“…En este sentido, numerosos estudios confirman el impacto negativo de la desnutrición, o la falta de soporte nutricional, en las complicaciones quirúr-gicas [10][11][12][13][14][15] , potencialmente prevenibles a través de intervenciones específicas [16][17][18][19][20] . La evaluación nutricional de los pacientes hospitalizados, y específicamente los pacientes oncológicos, es compleja, debido a múltiples factores que interfieren en las mediciones antropométricas y bioquímicas.…”
unclassified